Professional graphic design knowledge in Hong Kong: from graduate to professional. Issue 1 (2nd July 2016) - Cheung, Benson Pun Sin
Abstract: This article investigates the scope of graphic design professional knowledge in practice, and questions whether the knowledge and training provided at university are sufficient for graduates to become design professionals in Hong Kong. Official reports indicate that Hong Kong designers' competence is limited to skills of execution, contributing in general to a low standard of professionalism due to a lack of professional knowledge. Three kinds of respondents were involved in the study: graduate graphic designers, design firm employers, and design academics. The study relied on a mixed method approach, with the qualitative interview method as the core qualitative component and a survey as the supplementary quantitative component. Findings reveal the similarity of views held by the academics, employers and graduate designers interviewed: 'A professional designer is knowledgeable and performs well in both internal and external environment.' However, the graduate designers believe that aesthetic appearance and styling are the most important aspects of professional graphic design practice, which are above other knowledge aspects that help graphic design to function, such as marketing, business strategies and user's psychology. In addition, there is a 'knowledge gap' acknowledged by academics and graduates from academic training to practice. The academics and employers in Hong Kong are not sensitive enough to value the importance of such knowledge and training for graduates. The quantitative findings of this study truly reflect the criticism of Frascara: the historical development of graphic design has long overemphasized the importance of aesthetic appearance, styling and visual structure and neglected the importance of functionality. The results also highlight/draw attention to challenging areas worthy of future research: the content of graphic design professional knowledge and its professionalism in Hong Kong. Such research may unveil survival strategies for the graphic design profession.